2023
DOI: 10.3389/fcvm.2022.1013262
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Spike protein activates TMEM16F-mediated platelet procoagulant activity

Abstract: Thrombosis of the lung microvasculature is a characteristic of COVID-19 disease, which is observed in large excess compared to other forms of acute respiratory distress syndrome and thus suggests a trigger for thrombosis that is endogenous to the lung. Our recent work has shown that the SARS-CoV-2 Spike protein activates the cellular TMEM16F chloride channel and scramblase. Through a screening on >3,000 FDA/EMA approved drugs, we identified Niclosamide and Clofazimine as the most effective molecules at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 65 publications
(114 reference statements)
0
6
0
Order By: Relevance
“…Thereby, Reelin promotes platelet activation leading to thrombin generation and the formation of a fibrin clot. Since Reelin greatly increases with the severity of the infection, its prothrombotic function may participate in or aggravate the thromboembolic complications seen in COVID-19 patients ( 1 3 ), and may reflect an extensive platelet activation as seen in the severe forms ( 42 ) ( Figure 4 ). We have shown previously that Reelin promotes vascular adhesion and permeability to leukocytes, and in this article that Reelin expression in plasma is greatly elevated by ongoing inflammation anywhere in the body.…”
Section: Discussionmentioning
confidence: 99%
“…Thereby, Reelin promotes platelet activation leading to thrombin generation and the formation of a fibrin clot. Since Reelin greatly increases with the severity of the infection, its prothrombotic function may participate in or aggravate the thromboembolic complications seen in COVID-19 patients ( 1 3 ), and may reflect an extensive platelet activation as seen in the severe forms ( 42 ) ( Figure 4 ). We have shown previously that Reelin promotes vascular adhesion and permeability to leukocytes, and in this article that Reelin expression in plasma is greatly elevated by ongoing inflammation anywhere in the body.…”
Section: Discussionmentioning
confidence: 99%
“…As Clofazimine has demonstrated synergistic antiviral activity with other direct-acting antivirals, such as Remdesivir [ 5 ], we hope that fusion inhibitors with this mechanism of action may be considered for future synergistic drug combination therapies [ 15 ]. More recent mechanistic studies have also shown that Clofazimine is able to inhibit Spike-induced activation of TMEM16 and subsequent procoagulant activity [ 57 ]. This observation may increase clinical interest in using Clofazimine as an experimental drug in the treatment of COVID-19 infections with significant pulmonary thrombosis, or in the treatment of a range of other Spike-induced pathologies, potentially including the treatment of “long COVID” [ 58 , 59 , 60 , 61 , 62 , 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, enhancing endosomal pH and lowering intracellular Ca 2+ levels by niclosamide may both reduce viral uptake [ 23 , 25 , 84 ]. Finally, niclosamide inhibits the formation of pneumocyte syncytia and thrombus formation induced by the spike protein of SARS-CoV-2, which is due to the inhibition of ANO6 and possibly ANO1 [ 5 , 9 , 18 , 71 ]. Taken together, these findings support further evaluation of niclosamide for the use in inflammatory airway diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, ivermectin reduces viral infection by inhibiting importins, soluble transport receptors that are essential for the nucleo-cytoplasmic transit of substrates [ 17 , 51 , 59 ]. Niclosamide and ivermectin are suggested to inhibit ANO1 currents and ANO6-mediated phospholipid scrambling that is crucial for formation of multinucleated airway epithelial cells (syncytia) and blood clotting observed during SARS-CoV-2 infection and after vaccination against COVID-19 [ 9 , 18 , 71 ].…”
Section: Introductionmentioning
confidence: 99%